2011
DOI: 10.3399/bjgp11x593820
|View full text |Cite
|
Sign up to set email alerts
|

Influence of patient payment on antibiotic prescribing in Irish general practice: a cohort study

Abstract: BackgroundAntibiotics are widely believed to be overused and misused. Approximately 80% of all prescriptions for antibiotics are written by GPs. There are many external factors that influence a GP's decision to prescribe, including patient pressure. Access to primary care services operates on a two-tier system in the Republic of Ireland: General Medical Service (GMS) card holders have free access to GPs and medications; and non-card holders (private patients) must pay a non-subsidised fee to visit their GP. Ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 23 publications
1
21
0
Order By: Relevance
“…The majority of ROI citizens must pay a fee to visit their GP and this has shown as a possible influence on the GP’s decision to prescribe an antibiotic during the consultation [10]. …”
Section: Introductionmentioning
confidence: 99%
“…The majority of ROI citizens must pay a fee to visit their GP and this has shown as a possible influence on the GP’s decision to prescribe an antibiotic during the consultation [10]. …”
Section: Introductionmentioning
confidence: 99%
“…In the USA study most disease was seen in the relatively poor, but resistance was higher in the relatively rich. It is likely that access to healthcare as well as the presence of an infection is important in the risk of antimicrobial resistance; a study in Ireland showed patients treated privately were prescribed antibiotics more often than those treated by the public health system [30]. …”
Section: Discussionmentioning
confidence: 99%
“…In a study conducted in Ireland, Murphy et al note that private patients are significantly more likely to receive antibiotics than patients with state-funded access to health care. 6 It is possible, of course, that patients who pay may delay consultation with their GP, resulting in more severe illness and a consequent greater need for active treatment. However, it is also possible that these discrepancies may represent differences in the way in which patient expectations are managed, and strategies to reduce excessive antibiotic prescribing should take such factors into account.…”
Section: Inappropriate Medicinesmentioning
confidence: 99%